Designing vaccine candidates against dengue virus by in silico studies on structural and nonstructural domains. (June 2022) - Shoushtari, Mohammad; Mafakher, Ladan; Rahmati, Saman; Salehi-Vaziri, Mostafa; Arashkia, Arash; Roohvand, Farzin; Teimoori-Toolabi, Ladan; Azadmanesh, Kayhan
Abstract: One-third of the world's population is at risk of Dengue infection. Envelope domain 3 (EDIII) and nonstructural protein1 (NS1) proteins as the potent antigenicity regions for humoral immunity in addition to the bc loop region as a completely conserved region have been used for designing protective vaccines. We aimed to design vaccine candidates according to the bc loop, EDIII, and NS1 regions of Dengue serotype2 to be used as vaccine candidates for all serotypes of Dengue virus especially serotype 2. Firstly the bc loop region with EDII fragments at both ends as well as EDIII and NS1 regions were used which were linked with the GGGGS linker to the bc loop region. In two other strategies, the bc loop with EDII and NS1 fragments at both ends was used to increase its structural stability. Tertiary structure prediction and validation of vaccine constructs indicated that all vaccine constructs were modeled with high quality and stable structure during molecular dynamics simulation. B cell epitope mapping by Bepipred and ElliPro methods confirmed the existence of high potent epitopes in the bc loop, EDIII, and NS1 regions in both linear and conformational B cell epitopes. Furthermore, molecular docking for the bc loop region demonstrated that all designed vaccines have a higher affinity to interact with 1C19 monoclonal antibody than only the bc loop region or bc loop epitope in the protein EII. Our data of in silico studies indicated that the designed vaccines could effectively induce humoral immunity against four dengue serotypes. Graphical abstract: Image 1 Highlights: Vaccine candidates according to the bc loop, EDIII, and NS1 regions of Dengue serotype2 were designed. All vaccine constructs were modeled with high quality and stable structure during molecular dynamics simulation. B cell epitope mapping confirmed the existence of high potent epitopes in the bc loop, EDIII, and NS1 regions. All designed vaccines have a higher affinity to interact with 1C19 than only the bc loop region or this epitope in the protein EII. The designed vaccines could effectively induce humoral immunity against four dengue serotypes.